ACUTE POSTERIOR MULTIFOCAL PLACOID PIGMENT EPITHELIOPATHY AFTER IMMUNIZATION WITH MULTIPLE VACCINES. Issue Volume 16:Issues 1(2022) (January 2022) - Kraemer, Laura S.; Montgomery, Jay R.; Baker, Katherine M.; Colyer, Marcus H.
Abstract : Purpose: To report a case of acute posterior multifocal placoid pigment epitheliopathy occurring in temporal association with multiple immunizations in a previously healthy 25-year-old woman. Methods: Acute posterior multifocal placoid pigment epitheliopathy was diagnosed based on ophthalmological findings of bilateral placoid subretinal lesions complicated by a serous retinal detachment in the left eye. Results: Through HLA typing, the patient was found to possess the HLA-B*40 and HLA-DB1*15 alleles. She was treated with topical prednisolone acetate 1% and monitored for several months. The serous retinal detachment resolved, and visual acuity returned to normal. Conclusion: This case report adds to the body of knowledge regarding possible atypical interplay between vaccines and specific T-cell receptors of the host immune system and adds Polio and Tetanus to the growing list of vaccines potentially triggering acute posterior multifocal placoid pigment epitheliopathy. Increased awareness of the presentation of acute posterior multifocal placoid pigment epitheliopathy and that it may arise after immunization may also improve evaluation of acute changes in visual acuity. Abstract : Supplemental Digital Content is Available in the Text.To report a case of acute posterior multifocal placoid pigment epitheliopathy occurring in temporal association with multiple immunizations in a previously healthy 25-year-old woman.